Peran Digital Freelancer Marketplace dan Media Sosial Terhadap Perkembangan Gig Economy Worker - Masakazu, Kadek Masakazu; Ersi Sisdianto; Gede Suwardika; Dhimas Setyo Nugroho (Universitas Pendidikan Ganesha, 2023)
The Gig Economy Worker phenomenon is becoming an option for Generation Z to work; the problems that occur are the lack of attention from the Government in providing good guarantees for Gig Economy Workers, so it is necessary to conduct research that has the objective of How to Form Government Attention in Providing Social Security and Protection for Gig Economy Worker, What is the Role of the Digital Freelancer Marketplace in the Development of the Gig Economy Worker; What is the Role of Social Media on the Development of the Gig Economy Worker. The methodology in this study is that this type of research is analytic observational using a case-control or case-control research design. The results of this study show that there is still a need for more government attention because they do not provide social security and legal protection, and the results of the development of the Gig Economy, Workers are heavily influenced by the Digital Freelancer Marketplace and social media. This research has good implications for the development of science and illustrates that Gig Economy Workers are entitled to social security and protection where Gig Economy Workers work.